Syariat Islam dan Tradisi di Aceh Darussalam - M. Idris; Dinda Rizky Amalia (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2022)
This study describes Islamic law and traditions in Aceh Darussalam. This study aims to provide education to readers that Aceh Darussalam has many traditions based on Islamic law. This study uses a sociological study, namely research by examining applicable regulations and relating them to their application in people's lives based on developing phenomena. Islam and customs in Acehnese society are like substances and characteristics that cannot be separated from one another. Religion and culture are integrated in the way of life, social systems, culture, and Islamic values ​​which are now as if tradition must be separated from religion, and so religion must be separated from tradition. This arises from among those who study Islam with a rigid method, narrowing a meaning that should have a broad meaning, even claiming that it is forbidden to do something that the Prophet Muhammad never made. Islamic law in Aceh as we know it is very thick, in fact some of it has been running for a long time, even since the time of the Aceh sultanate, so that tradition continues to permeate and integrate with the daily life of the Acehnese people.